Plasma amyloid levels within the Alzheimer's process and correlations with central biomarkers. Issue 7 (16th February 2018) - Hanon, Olivier; Vidal, Jean‐Sébastien; Lehmann, Sylvain; Bombois, Stéphanie; Allinquant, Bernadette; Tréluyer, Jean‐Marc; Gelé, Patrick; Delmaire, Christine; Blanc, Fredéric; Mangin, Jean‐François; Buée, Luc; Touchon, Jacques; et al.
Abstract: Introduction: Diagnostic relevance of plasma amyloid β (Aβ) for Alzheimer's disease (AD) process yields conflicting results. The objective of the study was to assess plasma levels of Aβ42 and Aβ40 in amnestic mild cognitive impairment (MCI), nonamnestic MCI, and AD patients and to investigate relationships between peripheral and central biomarkers. Methods: One thousand forty participants (417 amnestic MCI, 122 nonamnestic MCI, and 501 AD) from the Biomarker of AmyLoïd pepTide and AlZheimer's diseAse Risk multicenter prospective study with cognition, plasma, cerebrospinal fluid (CSF), and magnetic resonance imaging assessments were included. Results: Plasma Aβ1–42 and Aβ1–40 were lower in AD (36.9 [11.7] and 263 [80] pg/mL) than in amnestic MCI (38.2 [11.9] and 269 [68] pg/mL) than in nonamnestic MCI (39.7 [10.5] and 272 [52] pg/mL), respectively ( P  = .01 for overall difference between groups for Aβ1–42 and P  = .04 for Aβ1–40 ). Globally, plasma Aβ1–42 correlated with age, Mini–Mental State Examination, and APOE  ε4 allele. Plasma Aβ1–42 correlated with all CSF biomarkers in MCI but only with CSF Aβ42 in AD. Discussion: Plasma Aβ was associated with cognitive status and CSF biomarkers, suggesting the interest of plasma amyloid biomarkers for diagnosis purpose.